Ship inner shell optimization based on the improved particle swarm optimization algorithm. (September 2018) - Guan, Guan; Yang, Qu; Gu, Wenwen; Jiang, Wenying; Lin, Yan
Highlights: Anew method for optimization of ship inner shell based on the improved particle swarm optimization algorithm is presented. Aparametric ship inner shell optimization model based on the parametric expression model of different types of ship inner shellis created. The particle swarm optimization algorithm is improved to solve this optimization model The feasibility of the method is verified by a 50000DWT product oil tanker Abstract: To improve the changeability of ship inner shell (SIS), so that both performance and design efficiency of transport ship can be improved, a new method for SIS optimization is proposed in this study. The method is based on the parametric expression model of SIS, which is a fully-associative model driven by dimensions. Based on the parameters of SIS, the computing system of hold capacity is developed to calculate the floating status and stability automatically. Furthermore, a parametric SIS optimization model is created, including optimization objective, constraints, optimization model solving etc., in which the maximized hold capacity and minimized ballast capacity are optimization objectives, the requirements and rules for SIS design are used as the constraints. The particle swarm optimization (PSO) algorithm is improved to solve this optimization model. The proposed method is applied to a 50, 000 DWT product oil tanker, and it is proved to be feasible, highly efficient, and engineering practical.